Persistence, seasonality, and fractional integration within a nonlinear framework: Evidence from US citizens' overseas travel. Issue 3 (May 2022) - Gil-Alana, Luis A; Payne, James E
This research note examines data on US citizens' overseas air passenger travel with respect to the degree of persistence, seasonality, nonlinearities, and fractional integration. Based on seasonally differenced data with allowance for autocorrelated errors, we find evidence of nonlinearity with moderate persistence and mean reversion in US overseas air travel. The results suggest that shocks to US overseas air travel will dissipate over time, and as such, the observed persistence and nonlinearity can provide useful information in the modeling and forecasting of future behavior.